Cronenberg, Flyness, and the Other-self - Beard, William (Cinémas, 1994)
David Cronenberg's recent work has shown a continuation of the same themes and motifs found in his exploratory and formative works of the 70s and early 80s. The relationship of mind and body, of rationality and flesh, of control and loss of identity, continues to be the dominating dichotomy of his cinematic world. But the relatively simple thematic oppositions of repression and explosion, and their relatively unexamined emotional underpinnings of ironic detachment and regurgitative disgust, of an early film like Shivers (1975) have given way in the 1980s to a much more complex and sensitive exploration of the causes and implications of Cronenberg's understanding of things. The author proposes, in this essay, to undertake a close examination of Cronenberg's 1986 film The Fly as a partial illustration of this process of continuation and refinement.